“Quid est homo quod memor es ipsius?” Calvin and Cocceius (1603–1669) on Psalm 8 - van Asselt, Willem J. (2011)
This article addresses a controversy between Reformed theologians on the exegesis of Psalm 8 which arose in the Dutch Reformed Church during the late seventeenth century. The followers of the Leiden theologian Johannes Cocceius proposed an eschatological (even apocalyptic) reading of this Psalm which was vehemently contested by the followers of the Utrecht professor Gisbertus Voetius. Both parties appealed to Calvin’s exegesis of this Psalm and argued that their opinions were in continuity with those of Calvin. By comparing Calvin’s exegesis of this Psalm to Cocceius’s explanation, it is possible to illuminate the seventeenth-century debate on this issue. This may also be instructive for explaining the variegated views on Biblical prophecy within the Reformed tradition. At the same time, an investigation of the sources of both theologians enables us to locate them in the history of exegesis.
Keywords: Bibel; Johannes Cocceius -- John Calvin -- history of exegesis -- exegesis of Psalm 8 -- Calvin’s historical versus Cocceius’s christological interpretation of Psalm 8 -- continuity and discontinuity in pre-critical Reformed exegesis of prophetical and apocalyptic texts